I leoni di Sicilia between Novel and TV Series (Altre Modernità, 2025)
This paper examines Stefania Auci’s novel I leoni di Sicilia and its television adaptation produced by Disney+. The study focuses on the narrative strategies employed in the novel and the transformations introduced in the TV series, highlighting changes in fictional chronology, narrative structure, and character development. By comparing the two works, the analysis explores how the Florio family saga has been adapted for an audiovisual audience, with particular attention to identity construction, generational conflicts, and the historical context. Additionally, the paper investigates the success of both the novel and the series, examining the factors that contributed to their popularity, including the appeal of family sagas and the fascination with the Sicilian setting.
Keywords: Florio; best-seller; adaptation; fictional chronology